Triptolide Attenuates Transplant Vasculopathy Through Multiple Pathways - Luo, Zihuan; Liao, Tao; Zhang, Yannan; Zheng, Haofeng; Sun, Qipeng; Han, Fei; Yang, Zhe; Sun, Qiquan (Frontiers in Immunology, 2020)
Transplant vasculopathy (TV), a hallmark of chronic allograft rejection, is the primary cause of allograft loss after organ transplantation. Because multiple mechanisms are involved in TV pathogenesis, effective therapy for it remains elusive. Here, we identify the role of triptolide, which has a wide spectrum of immuno-suppressive activities, in inhibiting TV development. Murine aortic transplants models were constructed and divided into triptolide-treated and untreated groups. We found that triptolide significantly alleviated intima thickening of allografts by inhibiting multiple pathways. Triptolide significantly reduced infiltration of T lymphocytes and macrophages and inhibited the levels of pro-inflammatory (TNF-α, IL-2, and IL-6) and pro-fibrotic factors (TGF-β, α-SMA, and MMP-9) in the graft. Additionally, triptolide significantly decreased the numbers of IFN-γ-producing T lymphocytes, as well as the expression of IFN-γ and IFN-γ-inducing factor (CXCL9 and CXCL10) in recipient. Moreover, triptolide decreased the numbers of B lymphocytes and plasma cells, as well as the levels of donor specific antibodies (DSAs) in recipient. Furthermore, triptolide not only inhibited vascular smooth muscle cell (VSMC) viability and promoted VSMC apoptosis but also significantly inhibited VSMC migration in vitro. These results emphasize the efficacy of triptolide in inhibiting TV development and provide a basis for developing new treatments to prevent TV-related complications and improve the long-term survival of transplant recipients.